Supply Chain Agility, Supplier Synergy, Cooperative Norms and Competitive Advantage: Mediating Role of Supplier Performance - Zainurossalamia, Saida; Hidayati, Tetra (International Journal of Supply Chain Management, 2020)
The prime focus of the present research is to examine the impact of cooperative norms, supplier synergy and supply chain agility on supplier performance and competitive advantage are examined. Furthermore, the mediating relationship of supplier performance among supplier synergy, supply chain agility, cooperative norms and competitive advantage is examined as well. The data is collected from the employees of the footwear industry in Indonesia. The sampling technique used was convenience sampling. Among the questionnaire distributed, 345 were usable to have a response rate of 55.64%. For the analysis of the collected data, PLS-SEM was used because it is sensitive for multivariate data. The findings of the study revealed that cooperative norms, supplier synergy and supply chain agility have a significant direct impact on supplier performance and competitive advantage. Moreover, supplier performance also mediates between supplier synergy, supply chain agility, cooperative norms and competitive advantage. The findings of the study are helpful for the academician and practitioners of the supply chain.